P002 Real-world experiences of biologic tapering. (26th April 2021) - Rutter-locher, Zoe; Man, Yik Long; Marsh, Lydia; Mercer, Scott; Menon, Bina; Cope, Andrew
Abstract: Background/Aims Biologic therapy and treat to target have significantly improved patient outcomes and we now have a proportion of patients on biologic therapy who remain in clinical remission. NICE guidance suggests "cautiously reducing drug doses or stopping drugs in those who have maintained the treatment target". Despite this guidance, little is known about current clinical practice of biologic tapering in UK rheumatology centres. We aimed to illustrate current practice and success rates in biologic tapering in a real-world setting in patients with rheumatoid arthritis (RA), psoriatic arthritis (PSA) and ankylosing spondylitis (AS). Methods We identified patients who were potentially suitable for biologic tapering 1 week prior to their follow up appointment using the following criteria - any anti-TNFα biologic ≥ 1 year, RA patients (DAS28 CRP<3.2, CRP normal), PSA patients (no swollen joints, CRP normal, no extra-articular manifestations), AS patients (BASDAI<4, CRP normal). We then analysed how many patients were successfully tapered at one year. Tapering schedule was decided by the supervising rheumatologist. Results From December 2018 to February 2019, 66 patients were identified as being suitable for biologic tapering. 3 patients did not attend and were excluded from further analysis. Tapered group: 20 (32%) patients were tapered. Based on the retrospective review of clinic letters, the "tapering schedule" was inconsistent and the information provided to patients if they flared was also inconsistent - 9 (45%) patients were advised to return to their normal dose and only 1 (5%) patient was advised to contact the helpline. After 12 months of follow up, 11 (55%) patients remained on the tapered dose, 7 (35%) patients returned to their prior dose and 2 (10%) patients were lost to follow up. Non-tapered group: 43 (68%) patients were not tapered. The reasons for not tapering were divided into 6 broad categories: active disease (n = 15, 35%), patient choice (n = 5, 12%), DMARD was tapered instead (n = 5, 12%), discuss at next visit (n = 3, 7%), reason not mentioned (n = 12, 28%), other (n = 3, 7%) Conclusion This Quality Improvement Project has highlighted the inconsistencies in biologic tapering in a UK real-world setting. In response to this inconsistency, we have developed a departmental guideline which provides stringent criteria to identify patients at lowest risk of flaring and standardises a tapering schedule and clinical pathway. We also created a patient information leaflet that could be distributed. Only half of the patients remained on the tapered dose after 1 year, suggesting a significant proportion of patients flare following dose reduction. However, our findings may be limited by small sample size. National guidance and a thorough audit based on this guidance is welcomed. Disclosure Z. Rutter-locher: None. Y. Long Man: None. L. Marsh: None. S. Mercer: None. B. Menon: None. A. Cope: None.